Pure yolk-sac tumor with XO/XY Turner’s syndrome mosaicism - Figueroa Zevallos, Víctor (2014)
Turner’s syndrome is a genetic disorder caused by lack of an X chromosome. In some cases it is present with XY mosaicism, with increased risk of malignant gonadal tumors. It is important to determine the presence of the Y chromosome to perform prophylactic removal of the dysgenetic gonads. We present the case of a patient with Turner’s syndrome 45,X0/46,XY mosaicism associated to pure giant yolk sac tumor. This association of malignancy in a patient with mixed gonadal dysgenesia is extremely rare.Keywords: Turner’s syndrome, mosaicism, gonadal dysgenesia gonadal, yolk sac tumor.